Is Cardiac Troponin I Valuable to Detect Low-Level Myocardial Damage in Congestive Heart Failure? - Şirin, Göktuğ (Sisli Etfal Hastan Tip Bul, 2019)
OBJECTIVES: Congestive heart failure (CHF) is a heart disease with a growing incidence and prevalence. Creatine kinase-myocardial base (CK-MB) is generally used to determine myocardial damage; however, it is insufficiently sensitive to measure the relatively low level of myocardial damage that typically occurs in heart failure (HF). The use of cardiac troponins, which are far more sensitive and specific, has become common to identify myocardial damage and permits the detection of even minute amounts of damage. The aim of this study was to ascertain whether cardiac troponin I (cTnI) can be used to detect low-level myocardial damage occurring in CHF in real-life conditions. METHODS: Fifty patients with CHF symptoms (Group I) and 20 patients who were evaluated as normal (Group II) were included in this prospective study. The Framingham criteria were used to diagnose HF. Group I was divided into 3 subgroups according to the New York Heart Association classification of functional capacity: Class II, Group A; Class III, Group B, and Class IV, Group C. On the first day of admission, CK-MB and cTnI levels were measured and assessed quantitatively. The cTnI level was compared between these 3 subgroups and between Groups I and II. Linear regression analysis was performed to investigate the relationship between ejection fraction (EF) and cTnI. RESULTS: The mean cTnI value was 0.084±0.07 ng/mL in Group I and 0.018±0.012 ng/mL in Group II (p=0.0001). The mean cTnI value was 0.047±0.016 ng/mL, 0.080±0.048 ng/mL, and 0.175± 0.102 ng/mL in Groups A, B, and C, respectively. The difference between the subgroups of Group I was statistically significant. In addition, it was observed that there was a significant difference in the EF (%) value between Groups I and II and between Groups A, B, and C. Linear regression analysis revealed an inverse relationship between EF and cTnI (r: -0.66) (p=0.0001). CONCLUSION: As the severity of HF increased, the cTnI serum level also increased. This increase was inversely related to the EF value. These results are consistent with other studies in the literature, suggesting that the cTnI level may be a useful marker in the diagnosis and evaluation of severity of HF.